Cantos brilhando nos escombros: roteiros da poesia de Alberto da Cunha Melo - Lucena, Karine Braga de Queiroz (2012)
This work presents the way by which two constant points in Alberto da Cunha Melo?s work (social and political poem, and metaphysical or existential poem) are ordered in Soma dos Sumos (1983), Poemas anteriores (1989), Medita??o sob os lajedos (2002) and O c?o de olhos amarelos (2006). First of all, we investigate the main precedents of Military Coup that marked the Pernambuco?s poets surging of 65?s Generation (in a sense, Alberto da Cunha Melo was their guide). Besides, we consider Heloisa Buarque de Hollanda, Flora S?ssekind and Silviano Santiago?s views about the rapport between post-64?s literary production and censorship. Starting from this historical event, we focus on literary movement?s adventures that marked cultural life in Pernambuco. Finally, the main criticism texts on Alberto da Cunha Melo?s work writted by Alfredo Bosi, M?rio H?lio, C?sar Leal, Bruno Tolentino, Claudia Cordeiro, Jos? N?umanne Pinto and so on are theorethical support by which we can analyse and understand his poems.